TRANSLATION SHIFT IN JOSTEIN GAARDER™S SOPHIE™S WORLD - Paradita, Zea Zahwa; Setiasari, Winda; Gultom, Feriyanti Elina (Universitas Negeri Medan, 2020)
The study deals with Translation Shift in Jostein Gaarder™s Sophie™s World. The objectives of the study were to find out the types of category shift that found in Sophie™s world. It also aims to describe the translation shift that affects the reader perception in the novel of Sophie™s world. The research method of this study used qualitative research. The sources data from both novel of source language and target language in Sophie™s World novel and also interviewed five informants who known about translation shift. The data were analyzed by using Catford™s theory. The findings of the study show that there were 4 types of category shift. Each types of category shift namely: (1) structure shift, (2) class shift, (3) unit shift, (4) intra system shift. Those category shifts occur because the grammatical systems of the Source Language and Target Language are different, that is why the translator is dictated by the target language. It also affects reader reception that cost of lack understanding base on expressing the real meaning.